A STUDY ON AWARENESS OF MOBILE MARKETING IN DHARMAPURI DISTRICT (International Journal of Scientific Research and Management (IJSRM), 2013)
Mobile marketing is defined as the use of the mobile medium as a means of marketing communications.It has gained momentum over the last several years. Its special features made it lucrative to various business concerns. Technological growth and increasing awareness amongst the consumers persuaded the Indian companies to evolve new strategies to reach the target audiences. Under these circumstances, a study has been conducted to identify the various segments of markets where the mobile marketing is in vogue and its acceptance by the consumers. Data was collected from consumers in Dharmapuri District and later factor analysis and cluster analysis were conducted to segment Dharmapuri District consumers. Demographic and technological variables were taken as criteria to segment the market. The revealed that certain variables distinguish market segments from each other. For the purpose of this study Dharmapuri District consumers were classified into three different segments, namely knowingly nonuser, the real accepter and the uninterested.